Fonologi Bahasa Bajau di Desa Tanjung Perepat Kecamatan Biduk-Biduk Kabupaten Berau - Dandi, Dandi; Hefni, Asnan; Putri, Nina Queena Hadi (Adjektiva: Educational Languages and Literature Studies, 2022)
The purpose of this study is to describe vocal phonemes, consonant phonemes, and diphttlefish found in Bajau language in Tanjung Perepat village. So that with this research can be one of the comparison materials to deepen the knowledge of regional language research, especially bajau language. This research was carried out in Tanjung Perepat village, Biduk-Biduk District, Berau Regency by using the listening method and capable methods in collecting research data and realized through SLC (Simak Libat Cakap) and CS (Cakap Semuka) techniques combined with record techniques and record techniques. Based on the presentation of data and data analysis obtained from the results of research on the Bajau language in Tanjung Perepat village, six vowel phonemes were found, namely: /a/, /e/, /ǝ/, /i/, /o/, and /u/. Sixteen consonant phonemes, namely: /b/, /c/, /d/, /g/, /h/, /j/, /k/, /l/, /m/, /n/, /ŋ/, /p/, /r/, /s/, /t/, and /w/. And diftong as many as three, namely: /ai/, /au/, and /iu/ which are classified as ascending diftong